Rekomendasi Pemupukan Fosfor dan Potasium berdasarkan Analisis Hara Tanah pada Tanaman Sayuran - Lutfi Izhar; Anas D. Susila (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2010)
ABSTRACTVegetables are important agricultural commodities. Productivity of vegetables in Indonesia is still low. One effort that can be done is an application of specific fertilizer recommendations. Fertilizer recommendation based on soil analysis is still rarely for vegetable crops and need further development. The purpose of this paper is to describe some fertilizer recommendations based on soil analysis for vegetable crops. Three stages to consider in the assessment of the research such as soil incubation, correlation test, calibration test and fertilizer recommendation statue. Application all this stages of soil method recommendation in Indonesia is still not widely applied. Two researches which were completed until the entire stage has been done for yard long beans and tomatoes. Recommendations for tomatoes on Inceptisols soil type with very low nutrient status of soil K was 180 kg K2O ha- 1, a low K soil nutrient status was 131.4 kg K2O ha-1, soil K nutrient status was 82.2 kg K 2O ha-1. Yard long bean that planted on Ultisol soil type with low soil P nutrient status was recommended by an application of 185.8 kg P2O5 ha-1, medium soil P nutrient status was added 174.9 kg P2O5 ha-1. Development of fertilizer recommendation based on soil testing to support agricultural development in Indonesia still has some problems and need some strategies for further research, application and dissemination in the future.Key words: vegetables, soil test, fertilizer recommendation